HIV‐1 and hijacking of the host immune system: the current scenario. Issue 10 (19th August 2016) - Imran, Muhammad; Manzoor, Sobia; Saalim, Muhammad; Resham, Saleha; Ashraf, Javed; Javed, Aneela; Waqar, Ahmed Bilal
Abstract : Human immunodeficiency virus (HIV) infection is a major health burden across the world which leads to the development of acquired immune deficiency syndrome (AIDS). This review article discusses the prevalence of HIV, its major routes of transmission, natural immunity, and evasion from the host immune system. HIV is mostly prevalent in Sub‐Saharan Africa and low income countries. It is mostly transmitted by sharing syringe needles, blood transfusion, and sexual routes. The host immune system is categorized into three main types; the innate, the adaptive, and the intrinsic immune system. Regarding the innate immune system against HIV, the key players are mucosal membrane, dendritic cells (DCs), complement system, interferon, and host Micro RNAs. The major components of the adaptive immune system exploited by HIV are T cells mainly CD4+ T cells and B cells. The intrinsic immune system confronted by HIV involves (apolipoprotein B mRNA‐editing enzyme, catalytic polypeptide‐like 3G) APOBEC3G, tripartite motif 5‐α (TRIM5a), terherin, and (SAM‐domain HD‐domain containing protein) SAMHD1. HIV‐1 efficiently interacts with the host immune system, exploits the host machinery, successfully replicates and transmits from one cell to another. Further research is required to explore evasion strategies of HIV to develop novel therapeutic approaches against HIV.